Advancing Social Enterprise through Collective Action: A Strategic Approach to Enhancing Social Value - Palupiningrum , Agustina Widi; Winoto, Joyo; Achsani, Noer Azam; Sunito, Satyawan (Indonesian Journal of Sustainability Accounting and Management, 2025)
Social enterprises (SEs) are organizational forms that integrate economic and social values. In Indonesia, SEs have experienced significant growth in terms of institutional forms, numbers, and the variety of social issues that they address. However, the predominance of individualized and fragmented initiatives has constrained their potential to contribute systematically to broader societal objectives, including social welfare, economic well-being, social justice, and sustainability. This study proposes a re-conceptualization of SE development by advancing the idea of a collective movement inspired by the principles and dynamics of social movements. Employing a qualitative research design, this study draws on in-depth interviews with 25 SE practitioners and activists across eight cities and regencies in Indonesia. Data were analyzed using NVivo software by comparing findings from the literature with field data collected through in-depth interviews, following a dialectical approach proposed by Van Der Burg (2008), to explore the interactions between social enterprises and social movements. The findings reveal three key patterns of interaction: (1) a dialectical relationship in which both SEs and social movements co-shape each other, (2) SEs as internalized spaces of movement-building, and (3) social movements as ecosystems that nurture and interconnect multiple SEs. This study also identifies five foundational principles—social values, resource mobility, organizational capacity, collective action, and shared purpose—as critical to enabling a movement-based approach to SE development. This approach fosters synergy among diverse actors, institutionalizes collaboration, and enhances the scalability and resilience of social impacts. Theoretically, this study contributes by offering a collective action framework for understanding SE evolution.